1967
DOI: 10.2337/diab.16.2.96
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Tolerance and Related Factors in Dogs Fed Diets of Suboptimal Protein Value

Abstract: Littermate dogs were fed from weaning on high-protein diets (HP) or on dietswhich were adequate in calories but marginally deficient in protein (LP). The LP animals grew at a slightly retarded rate but showed no other outward abnormality. In the HP animals, intravenous glucose tolerance (K) increased steadily up to twelve months of age (K = 6) and then declined to the adult value (K = 4.7). These changes were accelerated and exaggerated in LP dogs so that, from seven months onwards, the K values for the LP dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

1972
1972
1992
1992

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…Russell (I957), noting similar metabolic responses in starvation and after growth hormone administration, predicted that growth hormone would be raised in starvation, while Heard & Turner (1967) made a similar suggestion to account for the abnormal glucose tolerance in their protein deprived animals. On the other hand, Monckeberg et al (1963), possibly describing a different syndrome, claimed that malnourished children failed to respond to adequate dietary replacement unless growth hormone was concomitantly administered, which suggested growth hormone deficiency.…”
Section: G R O W T H H O R M O N Ementioning
confidence: 99%
See 3 more Smart Citations
“…Russell (I957), noting similar metabolic responses in starvation and after growth hormone administration, predicted that growth hormone would be raised in starvation, while Heard & Turner (1967) made a similar suggestion to account for the abnormal glucose tolerance in their protein deprived animals. On the other hand, Monckeberg et al (1963), possibly describing a different syndrome, claimed that malnourished children failed to respond to adequate dietary replacement unless growth hormone was concomitantly administered, which suggested growth hormone deficiency.…”
Section: G R O W T H H O R M O N Ementioning
confidence: 99%
“…Protein malnourished rats show a reduction in brain noradrenaline and dopamine (Shoemaker & Wurtman, 1971). Urinary metanephrines are reported as low in a small number of marasmic infants (Bourgeois et al, 1973) while in kwashiorkor, others have found elevated adrenaline and low dopamine excretion (Parra et al, 1973b;Hoeldtke & Wurtman, 1973). Urinary noradrenaline is unaltered while VMA excretion is diminished (Hoeldtke & Wurtman, 1973).…”
Section: P I T U I T a R Y -T H Y R O I D F U N C T I O Nmentioning
confidence: 99%
See 2 more Smart Citations
“…However, if dimunition of Beta-cell mass were to be shown, the case for protein deficiency in the aetiology of malnutrition-related diabetes would be strengthened [3]. Histopathological investigations of the endocrine pancreas of children who have died during the acute phase of kwashiorkor are confusing since hypertrophic [24][25][26][27][28] The stunting of growth, the impaired glucose tolerance and blunted insulin secretory response to glucose of kwashiorkor can be reproduced in animal models of proteinenergy malnutrition [36][37][38][39][40][41][42][43]. Following nutritional rehabilitation growth is resumed, glucose tolerance normalized but a lowered capacity for insulin secretion persists [41,42,44].…”
mentioning
confidence: 99%